PENGARUH GAYA KEPEMIMPINAN DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PAMULANG - Rika Astuti; Shella Puspita Sari (Journal of Research and Publication Innovation, 2025)
This research aims to determine the simultaneous influence of leadership style and workload on employee performance at the Pamulang District Office. The method used is quantitative associative. The research population was 61 people and all of them were the sample in this study. The data analysis techniques used are instrument testing, classical assumption testing, descriptive analysis, regression testing, correlation coefficient testing, coefficient of determination testing and hypothesis testing. The results of this research show that leadership style and workload have a positive and significant effect on employee performance, both partially and simultaneously. A company can achieve its goals if it has a good leader and employees receive a normal workload resulting in good performance.